(untitled) (REMUNOM, 2025)
This article provides a thorough analysis of the fundamental legal aspects surrounding the duplicate in the context of the commercial credit system, highlighting the relevance of Law No. 5,474, dated July 18, 1968, which deals with duplicates. Exploring its legal nature, the duplicate is highlighted as an essential credit instrument, governed by this specific legislation, characterized by its negotiable nature and enforceability once accepted by the debtor. Next, the formal and material requirements for the issuance of the duplicate are meticulously examined, emphasizing the importance of complying with these requirements for its legal validity and effectiveness as a credit instrument. A detailed analysis of the procedures for the acceptance of the duplicate by the debtor is presented, highlighting its legal and commercial implications, as well as the deadlines and formalities involved. Additionally, the steps for protesting the duplicate in case of default are addressed, emphasizing its relevance as a measure to protect the rights of the creditor and facilitate debt collection. Finally, this article aims not only to provide a comprehensive understanding of the norms and principles governing the duplicate in the business environment but also to highlight its importance as a vital instrument for the efficiency and security of commercial transactions.